Gastrodiplomasi Korea selatan dalam Upaya Nation Branding di Indonesia sebagai Negara Muslim Terbesar - Nadia Mahza Prameswari; Hermini Susiatiningsih; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
South Korea is one of the countries that has gone global through its Korean Wave in the form of K-Pop and K-Drama. From these two aspects, it then expanded with the emergence of K-Food products by the Indonesian people, most of whom are Muslim populations. Pop and K-Drama are followed by K-Food products. In an effort to nation branding in Indonesia as the largest Muslim country. The purpose of this study is to examine the formation of South Korea's strategy in nation branding efforts in Indonesia. In order to answer the problems and objectives of the research, the main concepts of gastrodiplomacy and SWOT analysis were used. The results show that gastrodiplomacy through Korean halal food can be an effort to brand South Korea in Indonesia as the largest Muslim country. The strategy is based on strengths, weaknesses, opportunities, and threats related to aspects of South Korean food. It is recommended that the South Korean government can continue to use K-Wave to increase the Korean halal food market, as well as collaborate with food entrepreneurs to adapt to market needs, especially in its efforts to obtain halal labeling so that the product can be expanded scale-wise.